PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN PINTAR UNTUK KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH DASAR - Yulia Darniyanti; Wiwik Okta Susilawati; Nanda Saspira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the problem of students who cannot read sentences correctly and some students cannot distinguish punctuation marks and are also not fluent in reading. The aim of this research is to produce smart board learning media that is valid, practical and effective. The type of research used is research and development (R&D) using the ADDIE development model which consists of 5 stages, namely analysis, desing, development, implementation, and evaluation stages. The results of the validity of the smart board media were validated by 4 validators, namely validation by content experts, the results obtained were 90% categorized as very valid. Validation by language experts obtained results of 91,66%, categorized as very valid. Media expert validation obtained a result of 90% categorized as very valid. Validation of the teaching module obtained a result of 91% categorized as very valid, validation of the teaching module by the teacher obtained a result of 100% categorized as very valid. The results of the practicality of smart board media through the teacher response questionnaire by class 1 teacher obtained a result of 100% which was categorized as very practical, while through the student response questionnaire an average result of 97,71% was categorized as very practical. The effectiveness result obtained and the results of student learning tests in main schools obtained an average of 90,32% categorized as very effective.